Minimal endoscopic changes in non-erosive reflux disease - RATIN,Ana Carolina Ferreira (2015)
BACKGROUND: Gastroesophageal reflux disease is an increasingly common condition worldwide causing a considerable economic impact. More than half the patients with clinical symptoms of reflux disease display no mucosal erosions on esophagogastroduodenoscopy, making it impossible to confirm the diagnosis without further investigations. AIM: To evaluate the correlation between minimal endoscopic changes on white-light esophagogastroduodenoscopy (carditis, mucosal thickening and invisibility of vessels) and histologic changes observed in distal esophageal biopsies in a sample of patients with symptoms suggestive of reflux disease, and to verify the specificity of these symptoms for non-erosive reflux disease. METHODS: Retrospective, cross-sectional study based on information retrieved from a digital database at a Brazilian hospital for the period March-October, 2012. The sample consisted of previously untreated, non-smoking subjects aged >18 years with symptoms suggestive of reflux disease but no esophageal erosions, submitted to esophagogastroduodenoscopy and distal esophageal biopsy. RESULTS: The final sample included 23 subjects. The most frequently observed change was invisibility of vessels (n=21; 91.3%), followed by mucosal thickening (n=15; 65.2%) and carditis (n=5; 21.7%). The correlation coefficient between each variable and the anatomopathological diagnosis was 0.386 for body mass index, 0.479 for mucosal thickening, -0.116 for invisibility of vessels, 0.306 for carditis and 0.462 for hiatal hernia. CONCLUSION: All patients displayed minimal endoscopic changes on esophagogastroduodenoscopy, but only mucosal thickening revealed a moderately significant correlation with severity of esophagitis, although increased body mass index values and the presence of hiatal hernia were also associated.